Perceptions of how spiritual leadership enhances connectedness in blended teams - Thandeka L. Maseme; Musawenkosi D. Saurombe (SA Journal of Human Resource Management, 2025)
Orientation: Before the coronavirus disease 2019 (COVID-19) pandemic, employees in most industries were expected to work from the office during their stipulated working hours. The pandemic notably changed this norm, creating unique challenges for managers who were not used to leading remote teams. Since then, hybrid work has become more common, and organisations have been trying out different hybrid models.